Comparative analysis of extraction technologies for plant extracts and absolutes - Cao, Shoutao; Liang, Jinchang; Chen, Mingguang; Xu, Chao; Wang, Xiaoqiang; Qiu, Lei; Zhao, Xianyan; Hu, Wenxiao (Frontiers in Chemistry, 2025)
Plant extracts and absolutes have high application value in several industries such as medicine, food, and fragrance. Especially in the field of fragrance, while there is expensive, they are prized by perfumers and provide a rich and lasting aroma. Owing to advancements in extraction technology, their yields have increased and their ingredients have become richer. However, no extraction technology is universal and each extraction technology has its own distinct advantages and disadvantages. Therefore, this review systematically characterizes the extraction technologies for plant extracts and absolutes, including traditional extraction technologies, such as maceration, percolation, reflux, and Soxhlet extraction, and green extraction technologies, such as microwave-assisted, ultrasonic-assisted, pressurized liquid, and supercritical fluid extractions. These extraction technologies are analyzed and compared in terms of their principles, advantages and disadvantages, improvement solutions, and applications. In addition, this review summarizes and compares new green extraction solvents and discusses the practical applications of these advanced extraction methods and solvents from different perspectives.